Determinants of inequalities in the quality of Brazilian diet: trends in 12-year population-based study (2003-2015) - Aline Veroneze de Mello; Flávia Mori Sarti; Jaqueline Lopes Pereira; Moisés Goldbaum; Chester Luiz Galvão Cesar; Maria Cecilia Goi Porto Alves; Regina Mara Fisberg (BMC, 2018)
Abstract Background Recent studies have explored the influence of socioeconomic inequalities on the diet quality. However, there is lack of evidence regarding the level of inequalities in dietary quality and its main contributing factors from population-based follow-up studies. The primary objective of this study was to investigate the level and the determinants of inequalities in diet quality in a representative sample of adolescents, adults and older adults resident in São Paulo, Brazil. Methods Data from the Health Survey of São Paulo (ISA-Capital) were analyzed for 2003 (n = 2398), 2008 (n = 1662) and 2015 (n = 1742) surveys. Information on food consumption was obtained through 24-h dietary recall, and diet quality was assessed based on the Revised Brazilian Healthy Eating Index (BHEI-R). The descriptive variables were compared using 95% confidence interval. The scores of BHEI-R and its components were compared across age groups and year. The association between socioeconomic inequalities and diet quality was based on the estimation of concentration index. Results We observed that the BHEI-R scores gradually improved over 12-years, with older adults showing the greatest improvement. The increase in overall population score was observed for total fruits, whole fruits, whole grains, oils and sodium. The main contributor to socioeconomic inequality in diet quality in 2003 was ethnic group, and in 2008 and 2015, it was per capita household income; age was a persistent factor of inequality in the population over the years. Concentration indices indicated that lower income individuals had higher BHEI-R scores in 2003; however, there was a shift in favor of higher income individuals in 2008 and 2015. Conclusions Changes in the patterns of determination of inequalities according to age, ethnic group or income during the period analyzed show the existence of ongoing process of contribution of demographic and socioeconomic factors in the diet quality of individuals in a large urban center.